Dynamic stresses in the impeller chambers of propeller turbines - Dem'yanov, V. A.; Ivanov, S. V. (Hydrotechnical Construction, 1997)
The problem of ensuring the reliable operation of the impeller chamber of a hydraulic turbine is of major importance from the standpoint of the fail-safe operation of the hydroelectric unit, since failure of one or several segments of the chamber will lead to long-term shutdown for repair. Restoration of the impeller chamber is a rather complex technical problem, since it is necessary to provide for a certain clearance between the chamber and impeller blades after the repair. In addition to failures that are fatigue in nature, the impeller chamber is subject to cavitation erosion. The set of the above-indicators leads to the fact that the actual impeller chamber exhausts its remaining life during operation, and modernization of hydraulic turbines is determined to a large degree by the need for replacement of the chamber. The stress--strain state of the impeller chamber had not been assessed until recently, since it was considered that the latter is not a bearing structure and all loads acting on it are transmitted onto the basic concrete of the block. After failures of impeller chambers at certain hydroelectric plants, it is recently recommended in design not to focus attention on the surrounding concrete to ensure reliability, and not to assume that the impeller chamber takes up the hydrodynamic loads completely.